Fearless fighter : an autobiography - Chirwa, Vera Mlangazuwa (Zed Books, 2007)
Vera Chirwa's life embodies African struggles against colonialism and corruption. This powerful and moving book celebrates her achievements as a campaigner, politician, lawyer, wife and mother, and calls for greater awareness of the risks faced by human rights defenders everywhere.